Similarities in mRNA expression of peripheral blood drug metabolizing enzymes and cancer marker genes with biopsy samples of head and neck cancer patients. (18th August 2019) - Hasan, Feza; Katiyar, Tridiv; Maurya, Shailendra S.; Yadav, Vinay; Yadav, Sanjay; Pandey, Rahul; Mehrotra, Divya; Hadi, Rahat; Singh, Sudhir; Bhatt, Madan L.; Parmar, Devendra
Abstract: Purpose: To develop peripheral blood mRNA expression profiles of drug metabolizing enzymes (DMEs) as a surrogate to monitor tobacco induced head and neck squamous cell carcinoma (HNSCC), attempts were made to investigate (i) similarities in alterations with the cancer marker genes in biopsy samples and (ii) if alterations similar to that seen in biopsy samples are reflected in peripheral blood. Methods: Total RNA from eight soft gingival tissues and eight biopsy samples of HNSCC patients and total DNA and RNA from blood of healthy controls ( n = 150) and HNSCC patients ( n = 150) was processed for expression and genotyping studies. Blood from patients receiving chemo-radiotherapy was processed for follow-up study. Results: qRT-PCR revealed significant increase in mRNA expression of DMEs in biopsy and blood samples of HNSCC patients when compared to controls. Similar alterations were observed in cancer marker genes in these samples. Patients with variant genotypes of DMEs showed greater magnitude of alterations in mRNA expression when compared to wild type controls. Responders of chemo-radiotherapy showed significant decline in induction of mRNA expression of DMEs and cancer marker genes Conclusions: The data suggest that peripheral blood expression profiles could be used to monitor tobacco-induced HNSCC as well as the treatment response.